The Influence of Authoritarian Leadership Style and Work Discipline on the Performance of Lamongan Regency Government Employees - Rizqi, Bela May Vita; Santoso, Mohammad Heru Budi; Novitasari, Diah Ayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This writing aims to determine the relationship between work discipline and the performance of government employees in Lamongan Regency who are subject to an authoritarian leadership style. This quantitative writing sample consisted of 62 respondents collected at the Lamongan District Fisheries Service. Documentation and questionnaire techniques were used to collect data for this writing. Assessment of the validity and reliability of instruments, multiple linear regression analysis, calculation of the coefficient of determination, hypothesis testing through partial and simultaneous trials, are used as data analysis methods. Based on the writing findings, employee performance is significantly influenced by authoritarian leadership and work discipline. The performance of employees at the Lamongan District Fisheries Service is mainly influenced by authoritarian leadership.